Identification of promising lactic acid bacteria for the fermentation of lupine‐ and faba bean‐based substrates to produce refreshing protein‐rich beverages—A strain screening - Stefan Ritter; Carolin Luber; Martina Gastl; Thomas Becker (Food Frontiers)
Abstract Lupines and faba beans are rising stars among legumes as sources of valuable, vegan plant‐based proteins. To enter new application areas like the production of protein‐rich refreshing beverages, the typical beany aroma impression has to be overcome, and the sensory appearance has to be improved, as it can be accomplished with lactic acid fermentation. An extensive strain screening of 70 lactic acid bacteria from 16 genera was performed to identify suitable strains to transform substrates made from lupines and faba beans into refreshing beverages and to improve their sensory characteristics. By analyzing carbohydrate utilization, production of organic acids and aroma compounds, and sensory appearance, 22 strains for lupine and eight strains for faba bean were preselected. Subsequently, the most suitable strains (five for lupine and three for faba beans) were identified by a trained sensory panel, and finally their growth kinetics were discussed. Generally, the aroma profile varied highly with the utilized strain. However, by selecting suitable strains, the beany impression can be highly reduced and pleasant aroma impressions (e.g., fruity and buttermilk) can be added. Most strikingly, it was proven that using germinated lupines and faba beans instead of raw ones can bypass the usual growth restriction, and the strain selection can be focused exclusively on sensory aspects. This opens the option to use strains usually excluded for the fermentation of legumes due to their lack of utilization of the legume‐typical α‐galactosides.